Confinement and Cross-Linking of 1,2-Polybutadiene in Two Dimensions at the Air-Water Interface - Vaillard, Anne-Sophie (Langmuir : the ACS journal of surfaces and colloids, 2020)
Langmuir monolayers of 1,2-polybutadiene (PB) were investigated by means of surface pressure-area isotherms, Brewster angle microscopy (BAM) observations, and sum-frequency generation (SFG) spectroscopy. A homogeneous and stable monolayer is formed 1.5 h after PB spreading provided that both light and oxygen are present. This was attributed to a slight oxidation of the PB at the air-water interface. The cross-linking of PB under UV photoirradiation was then studied. SFG spectroscopy demonstrates the in situ formation of a two-dimensional network. From surface pressure-area characterizations and BAM experiments, the cross-linked PB monolayer appears significantly denser and more rigid than the non-irradiated monolayer. Atomic force microscopy images reveal an increase by a factor of three in the root-mean-square roughness of the irradiated monolayers compared with the non-irradiated ones